The effects of teacher training on Filipino ethnic Chinese Episcopalian lay adults and their students - Tanhuanco, Patrick, 1954- (Denver, Colorado : Denver Seminary, 2002)
When one mentions the training of Filipino ethnic Chinese Episcopalian lay people, one also has to mention the historical background of the Chinese in the Philippines, how the Chinese attitudes toward church leadership and lay ministry were affected alongside the Filipinos during the four hundred years of Spanish colonization. one has to mention the coming of the Anglican-Episcopal Church to the Philippines, and how it in some ways reinforced the attitudes carried over from the Spanish regime, which brought about the problem this thesis is addressing.
In partial fulfillment of the requirements for the Degree Doctor of Ministry
A thesis of the professional project presented to the faculty of the Denver Seminary
Thesis (D.Min.)-Denver Seminary
Keywords: Teachers training of; Teaching